Cross‐Sectional Associations of Objectively Measured Sedentary Time, Physical Activity, and Fitness With Cardiac Structure and Function: Findings From the Dallas Heart Study - Thangada, Neela D.; Patel, Kershaw V.; Peden, Bradley; Agusala, Vijay; Kozlitina, Julia; Garg, Sonia; Drazner, Mark H.; Ayers, Colby; Berry, Jarett D.; Pandey, Ambarish (Journal of the American Heart Association, 2021)
Background Physical inactivity and low cardiorespiratory fitness (CRF) are associated with higher risk of heart failure. However, the independent contributions of objectively measured sedentary time, physical activity, and CRF toward left ventricular (LV) structure and function are not well established. Methods and Results We included 1368 participants from the DHS (Dallas Heart Study) (age, 49 years; 40% men) free of cardiovascular disease who had physical activity and sedentary time measured by accelerometer, CRF estimated from submaximal treadmill test, and cardiac magnetic resonance imaging performed using 3-T magnetic resonance imaging. A series of linear regression models were constructed to evaluate the associations of sedentary time, moderate physical activity, vigorous physical activity, and CRF with LV parameters after adjustment for established cardiovascular risk factors. We observed a modest correlation between CRF levels and objectively measured moderate (correlation coefficient, 0.17; <0.001) and vigorous physical activity (correlation coefficient, 0.25; <0.001) levels. In contrast, sedentary time was not associated with CRF. In adjusted analysis, both vigorous physical activity and higher CRF were significantly associated with greater stroke volume, LV mass, LV end-diastolic volume, and lower arterial elastance, independent of other confounders. Sedentary time and moderate physical activity levels were not associated with LV parameters. Conclusions Vigorous physical activity and CRF are significantly associated with cardiac structure and function parameters. Future studies are needed to determine if interventions aimed at improving CRF levels may favorably modify cardiac structure and function.